Rencana Pembangunan Makan Bergizi Gratis Dalam Upaya Peningkatan Kualitas Pendidikan Dan Kesehatan Anak Di Indonesia - Dian Tazkiya; Khaira Amalina; Naila Nur Fadhya; Samdarawita Samdarawita; Teuku Zulkarnain (Jurnal Sosial Humaniora Sigli, 2025)
The Free Nutritious Meal Program (MBG) is one of the Indonesian government’s priority policies under President Prabowo Subiant’s administration, aimed at reducing stunting rates, improving children’s health, and enhancing the overall quality of education. The program was initiated in response to the persistent issues of malnutrition and unequal access to education, with approximately 21.5% of Indonesian children still suffering from stunting. MBG serves not only as a nutritional intervention but also as a socio-economic strategy to strengthen human resources and promote educational equity. This study employs a qualitative descriptive approach, collecting primary data through in-depth interviews with teachers, school principals, health workers, and local government representatives involved in the implementation of MBG. Secondary data were obtained from official reports by relevant ministries and agencies, as well as scientific publications. Data analysis was conducted through the stages of data reduction, presentation, and conclusion drawing, with validation ensured by triangulation of sources and methods. The findings indicate that the implementation of the MBG program has had positive impacts on improving children’s nutritional status, reducing stunting rates, and increasing students’ motivation and learning concentration. The program also generates significant economic effects by involving local farmers, MSMEs, and cooperatives as food suppliers, thereby creating a multiplier effect for regional economies. However, several challenges remain, including limited funding, uneven distribution, and inadequate infrastructure. Overall, the MBG program is considered a strategic initiative to build a healthy, intelligent, and competitive generation while strengthening the synergy between the education, health, and economic sectors.  Program Makan Bergizi Gratis (MBG) merupakan salah satu kebijakan prioritas pemerintah Indonesia di bawah kepemimpinan Presiden Prabowo Subianto yang bertujuan untuk menurunkan angka stunting, meningkatkan kesehatan anak, serta mendukung peningkatan kualitas pendidikan nasional. Latar belakang munculnya program ini didasari oleh tingginya angka kekurangan gizi dan ketimpangan akses pendidikan di Indonesia, di mana sekitar 21,5% anak masih mengalami stunting. Program ini tidak hanya berfungsi sebagai intervensi gizi, tetapi juga sebagai strategi sosial-ekonomi untuk memperkuat sumber daya manusia dan pemerataan pendidikan. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data primer melalui wawancara mendalam dengan guru, kepala sekolah, tenaga kesehatan, serta instansi pemerintah daerah yang terlibat dalam pelaksanaan MBG. Data sekunder diperoleh dari laporan resmi kementerian dan lembaga terkait, serta publikasi ilmiah. Analisis data dilakukan melalui tahapan reduksi, penyajian, dan penarikan kesimpulan, dengan validasi menggunakan triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa pelaksanaan Program MBG memberikan dampak positif terhadap peningkatan status gizi anak, penurunan angka stunting, serta peningkatan semangat dan konsentrasi belajar siswa. Program ini juga memiliki efek ekonomi yang luas dengan melibatkan petani, UMKM, dan koperasi lokal sebagai pemasok bahan pangan, sehingga menciptakan multiplier effect bagi perekonomian daerah. Namun demikian, sejumlah kendala masih ditemui, seperti keterbatasan anggaran, ketimpangan distribusi, dan kesiapan infrastruktur. Secara keseluruhan, Program MBG dinilai sebagai langkah strategis dalam membangun generasi sehat, cerdas, dan berdaya saing, sekaligus memperkuat sinergi antara sektor pendidikan, kesehatan, dan ekonomi nasional.